Increasing Integration Density of Photonic Integrated Circuits by Employing Optimized Dielectric Metamaterial Structures - Andraz Debevc (IEEE, 2021)
All-dielectric metamaterial structures in the role of the cladding of optical waveguides (WGs) in photonic integrated circuits (PICs) are investigated and optimized by means of numerical simulations to increase the integration density of PICs. First the role of the refractive index (material platform) on the effects of metamaterial cladding is studied. The results of a quantitative analysis show that only material platforms with a high refractive index contrast (such as existing Si or membrane InP platform) can noticeably benefit from optimized metamaterial cladding in terms of integration density. Furthermore, we perform a comprehensive optimization of the geometry of metamaterial claddings in Si platform to achieve the lowest possible gap width between cores of two adjacent WGs, while keeping the cross-talk bellow the targeted limit of −30 dB at the length of 2 mm. By doing this we can, for the first time, explicitly show how much the integration density of a PIC can be increased. We demonstrate that a metamaterial cladding can, in best case, reduce the gap width by 60% compared to Si WGs with normal cladding in case of 450 nm wide core. The wavelength dependence and sensitivity to fabrication variability are also studied, revealing a trade-off between the lowest possible integration density and usable wavelength range. We show that a sizable decrease in gap width at a wide usable wavelength range is possible, demonstrating that waveguides with metamaterial cladding have the potential to be utilized in future applications requiring a high integration density of PICs.